ANANALYTICAL STUDY OF MARBLE CONSOLIDATION BY OXALATE PRECIPITATION USING DENSITY, FTIR AND POWDER-XRD MEASUREMENTS - Terzu, R.; Baraj, E.; Yu, S.; Förester, C.; Kropf, H.; Xhaxhiu, K.; Come, M. (Journal of Engineering & Processing Management, 2016)
Our recent study on consolidation of marble samples with the purpose of culture heritage protection occurred by periodical calcium oxalate precipitation on top of quasi parallelepipedic samples. The overall process consisting of three stages of treatment, starting with 5 % calcium acetate solution for 60 minutes at 20°C, a draining step at 70°C for 30 min, followed by a treatment with 5 % ammonium sulfate solution, it followed with the third stage which includes the treatment with 5% ammonium oxalate solution revealed a continuous density increace, determined using ethanol. As the natural samples had an initial density of 2.5871 g/cm3 , it increased up to 2.6980 g/cm3 for 50 times treatments. The precipitation of oxalate on top of calcium carbonate substrate, in form of calcite, revealed two distinguished infra-red bands, at 1316 cm-1 and 1624 cm-1 unsymmetrically located around the carbonate one at 1426 cm-1 .The intensity of the bands was proportional to the number of treatments. The continuous surface coverage investigated in parallel by powder XRD evidenced the presence of whewellite crystallites deposited on top of calcite, and their intensity increasing as well with the number of treatments. This method exhibits a reliable oxalate coverage of marble sample surfaces which doesn’t influence considerably their water solubility.